Green fluorescent proteins show divergent patterns among species and strains of Porites from the Great Barrier Reef - Samantha Goyen; Erin E. Chille; Timothy G. Stephens; Shrinivas Nandi; Line K. Bay; Debashish Bhattacharya (Coral Reefs, 2026)
GFP-like and RFP-like proteins serve diverse functional roles in corals, including photoprotection, prey capture, and algal symbiont attraction. This study investigated the diversity of biofluorescence patterns in 27 coral colonies of Porites cf. lutea and Porites cf. lobata from the Great Barrier Reef, Australia. We used comparative methods to characterize the extant fluorescence patterns under blue and green light for excitation, their relationship to the Porites phylogeny built using host animal 18S-28S rDNA sequence data. We also studied the impact of thermal stress on green and red fluorescence in a single coral genotype to assess stability of the observed signal. Overall, we identified six broad fluorescence patterns: star, uniform, absent, tentacles, oral region, and tentacle tips. Population analyses demonstrate that a single lineage of Porites may express divergent and distinct GFP-like patterns that are shared by all polyps in a colony. This suggests that biofluorescent proteins may confer an array of adaptive functions that allow Porites species to thrive in different ecosystems under different stressors. The reorganization of both green and red fluorescence distributions to uniform patterning under thermal stress suggests these proteins may provide a biomarker of thermal stress. Thus, the potential for GFP/green fluorescence and RFP/red fluorescence screening as a non-invasive tool to assess reef health and adaptive responses warrants further investigation, particularly in the context of climate change-driven stress events.

Symbiodiniaceae shifts over the last decade on the hottest coral reefs on Earth - Anna Fiesinger; Rachel Alderdice; Luigi Colin; Hannah Manns; Gabriela Perna; Kathryn H. Stankiewicz; Jacob J. Valenzuela; Line K. Bay; Daniel J. Barshis; Nitin S. Baliga; Iliana B. Baums; John A. Burt; et al. (Coral Reefs, 2025)
Corals in the Persian/Arabian Gulf (PAG) are resilient to various stressors, whose levels exceed those of coral reefs globally. These corals thereby offer insight into mechanisms underlying thermal resilience, e.g., regarding the role of endosymbiotic microalgae in the family Symbiodiniaceae. Previous studies have identified the thermotolerant species Cladocopium thermophilum as broadly associated with corals in the southern PAG. However, algal-host specificity at the within-species level and the temporal stability of these associations are not well understood. Here we sampled two dominant stony corals ( Porites harrisoni , n = 119 and Platygyra daedalea , n = 79) at three sites in the southern PAG and the neighboring Gulf of Oman (GO) to explore algal symbiont assemblage and specificity, whereby a prior dataset provided the opportunity to assess symbiont community stability in P. daedalea across a decadal time frame. Using high-throughput ITS2 marker gene sequencing and the SymPortal framework, we identified distinct, largely non-overlapping ITS2 type profiles of C. thermophilum as the dominant symbiotic partners in P. harrisoni and P. daedalea in the southern PAG, highlighting high host fidelity at the subspecies level. Despite this, we observed notable changes in C. thermophilum genotype diversity and an overall decrease over the course of a decade. By comparison, algal symbiont diversity in the neighboring GO corals increased, with formerly prevalent ITS2 type profiles being replaced by novel genotypes. Decadal data on P. daedalea suggest a shift in algal symbiont assemblage signified by the decline of formerly dominant algal type profiles and the emergence of novel genotypes. It is currently unknown whether the respective coral colonies associated with novel algae or became rare or extinct themselves. Understanding long-term algal population dynamics is critical to forecast how algal lineage loss or, alternatively, an increase in algal diversity will impact coral resilience and survival.

A Genetic Variant of Delta‐9 Desaturase Is Associated With Latitudinal Adaptation in a Coral from the Great Barrier Reef - Kristina L. Black; Line K. Bay; Mikhail V. Matz (Molecular Ecology, 2025)
Coral populations across the Great Barrier Reef (GBR) could rapidly adapt to the warming climate if they have standing genetic variation for thermal tolerance. Here, we describe a locus likely involved in latitudinal adaptation of Acropora millepora . This locus shows a steep latitudinal gradient of derived allele frequency increasing at higher latitudes, and harbours a cluster of eight tandemly repeated Δ9‐desaturase genes adjacent to a region in the genome where a hard selective sweep likely occurred. In colonies reciprocally transplanted across 4.5° of latitude, the expression of Δ9‐desaturase is upregulated at the high‐latitude reef. Furthermore, corals from the low‐latitude reef bearing the derived Δ9‐desaturase allele express the gene more and grow faster than their peers when transplanted to the high‐latitude reef. In other organisms ranging from bacteria to fish, Δ9‐desaturase is upregulated under cold conditions to adjust membrane fluidity by introducing double bonds into fatty acid chains of membrane lipids. It is therefore plausible that the signal of latitudinal adaptation at the Δ9‐desaturase locus is due to its involvement in adaptation to cooler temperatures at higher latitudes.

Chromosomal inversions harbour excess mutational load in the coral, Acropora kenti , on the Great Barrier Reef - Jia Zhang; Nadja M. Schneller; Matt A. Field; Cheong Xin Chan; David J. Miller; Jan M. Strugnell; Cynthia Riginos; Line Bay; Ira Cooke (Molecular Ecology, 2024)
The future survival of coral reefs in the Anthropocene depends on the capacity of corals to adapt as oceans warm and extreme weather events become more frequent. Targeted interventions designed to assist evolutionary processes in corals require a comprehensive understanding of the distribution and structure of standing variation, however, efforts to map genomic variation in corals have so far focussed almost exclusively on SNPs, overlooking structural variants that have been shown to drive adaptive processes in other taxa. Here, we show that the reef‐building coral, Acropora kenti , harbours at least five large, highly polymorphic structural variants, all of which exhibit signatures of strongly suppressed recombination in heterokaryotypes, a feature commonly associated with chromosomal inversions. Based on their high minor allele frequency, uniform distribution across habitats and elevated genetic load, we propose that these inversions in A . kenti are likely to be under balancing selection. An excess of SNPs with high impact on protein‐coding genes within these loci elevates their importance both as potential targets for adaptive selection and as contributors to genetic decline if coral populations become fragmented or inbred in future.

Dissecting coral recovery: bleaching reduces reproductive output in Acropora millepora - Nico D. Briggs; Cathie A. Page; Christine Giuliano; Cinzia Alessi; Mia Hoogenboom; Line K. Bay; Carly J. Randall (Coral Reefs, 2024)
Increasingly frequent and severe bleaching events driven by climate change are decreasing coral populations worldwide. Recovery of these populations relies on reproduction by the survivors of such events including local and upstream larval sources. Yet, corals that survive bleaching may be impaired by sublethal effects that suppress reproduction, reducing larval input to reefs, and consequently impeding recovery. We investigated the impact of the 2020 mass-bleaching event on Acropora millepora reproduction on inshore, turbid reefs in Woppaburra sea Country (the Keppel Islands), to improve our understanding of the effects of bleaching on coral populations. A. millepora experienced high bleaching incidence but low mortality across the island group during this event and thus constituted an ideal population to investigate potential sublethal effects on reproductive output. Six months after the heat wave, and just prior to spawning, we collected, decalcified, and dissected samples from 94 tagged A. millepora colonies with a known 2020 bleaching response, to investigate the relationships between stress severity and reproduction. Despite having regained their pigmentation, we detected a significant reduction in fecundity in colonies that had bleached severely. Considering the impact of the bleaching event on the coral population sampled (i.e., mortality, bleaching severity and colony size), coupled with reductions in fecundity, we estimated a total decrease in population-level reproductive output of 21%. These results suggest that reduced reproductive output may impact recovery of coral populations following bleaching and should be considered alongside traditional estimates of coral mortality.

Symbiodiniaceae diversity varies by host and environment across thermally distinct reefs - Magena R. Marzonie; Matthew R. Nitschke; Line K. Bay; David G. Bourne; Hugo B. Harrison (Molecular Ecology, 2024)
Endosymbiotic dinoflagellates (Symbiodiniaceae) influence coral thermal tolerance at both local and regional scales. In isolation, the effects of host genetics, environment, and thermal disturbances on symbiont communities are well understood, yet their combined effects remain poorly resolved. Here, we investigate Symbiodiniaceae across 1300 km in Australia's Coral Sea Marine Park to disentangle these interactive effects. We identified Symbiodiniaceae to species‐level resolution for three coral species ( Acropora cf humilis, Pocillopora verrucosa , and Pocillopora meandrina ) by sequencing two genetic markers of the symbiont (ITS2 and psbA ncr ), paired with genotype‐by‐sequencing of the coral host (DArT‐seq). Our samples predominantly returned sequences from the genus Cladocopium , where Acropora cf humilis affiliated with C3k, Pocillopora verrucosa with C. pacificum , and Pocillopora meandrina with C. latusorum . Multivariate analyses revealed that Acropora symbionts were driven strongly by local environment and thermal disturbances. In contrast, Pocillopora symbiont communities were both partitioned 2.5‐fold more by host genetic structure than by environmental structure. Among the two Pocillopora species, the effects of environment and host genetics explained four times more variation in symbionts for P. meandrina than P. verrucosa. The concurrent bleaching event in 2020 had variable impacts on symbiont communities, consistent with patterns in P. verrucosa and A. cf humilis , but not P. meandrina . Our findings demonstrate how symbiont macroscale community structure responses to environmental gradients depend on host species and their respective population structure. Integrating host, symbiont, and environmental data will help forecast the adaptive potential of corals and their symbionts amidst a rapidly changing environment.

Maximizing the utility of cryopreservation as an enabling technology in coral reef recovery and resilience - Jonathan Daly; Rebecca Hobbs; Andrea Severati; Mikaela Nordborg; Line Bay; Nikolas Zuchowicz; Mary Hagedorn; Justine O'Brien (Cryobiology, 2023)

The effects of marine heatwaves on acute heat tolerance in corals - Magena R. Marzonie; Line K. Bay; David G. Bourne; Andrew S. Hoey; Samuel Matthews; Josephine J. V. Nielsen; Hugo B. Harrison (Global Change Biology, 2023)
Scleractinian coral populations are increasingly exposed to conditions above their upper thermal limits due to marine heatwaves, contributing to global declines of coral reef ecosystem health. However, historic mass bleaching events indicate there is considerable inter‐ and intra‐specific variation in thermal tolerance whereby species, individual coral colonies and populations show differential susceptibility to exposure to elevated temperatures. Despite this, we lack a clear understanding of how heat tolerance varies across large contemporary and historical environmental gradients, or the selective pressures that underpin this variation. Here we conducted standardised acute heat stress experiments to identify variation in heat tolerance among species and isolated reefs spanning a large environmental gradient across the Coral Sea Marine Park. We quantified the photochemical yield ( F v /F m ) of coral samples in three coral species, Acropora cf humilis , Pocillopora meandrina , and Pocillopora verrucosa , following exposure to four temperature treatments (local ambient temperatures, and + 3°C, +6°C and + 9°C above local maximum monthly mean). We quantified the temperature at which F v /F m decreased by 50% (termed ED50) and used derived values to directly compare acute heat tolerance across reefs and species. The ED50 for Acropora was 0.4–0.7°C lower than either Pocillopora species, with a 0.3°C difference between the two Pocillopora species. We also recorded 0.9°C to 1.9°C phenotypic variation in heat tolerance among reefs within species, indicating spatial heterogeneity in heat tolerance across broad environmental gradients. Acute heat tolerance had a strong positive relationship to mild heatwave exposure over the past 35 years (since 1986) but was negatively related to recent severe heatwaves (2016–2020). Phenotypic variation associated with mild thermal history in local environments provides supportive evidence that marine heatwaves are selecting for tolerant individuals and populations; however, this adaptive potential may be compromised by the exposure to recent severe heatwaves.

A decade of coral biobanking science in Australia - transitioning into applied reef restoration - Rebecca J. Hobbs; Justine K. O'Brien; Line K. Bay; Andrea Severati; Rebecca Spindler; E. Michael Henley; Kate M. Quigley; Carly J. Randall; Madeleine J. H. van Oppen; Virginia Carter; Nikolas Zuchowicz; Mary Hagedorn; et al. (Frontiers in Marine Science, 2022)
Active restoration or intervention programs will be required in the future to support the resilience and adaptation of coral reef ecosystems in the face of climate change. Selective propagation of corals ex situ can help conserve keystone species and the ecosystems they underpin; cross-disciplinary research and communication between science and industry are essential to this success. Zoos and aquaria have a long history of managing ex situ breed-for-release programs and have led the establishment of wildlife biobanks (collections of cryopreserved living cells) along with the development of associated reproductive technologies for their application to wildlife conservation. Taronga Conservation Society Australia’s CryoDiversity Bank includes cryopreserved coral sperm from the Great Barrier Reef, which represents the largest repository from any reef system around the globe. This paper presents results from an inventory review of the current collection. The review highlighted the skew toward five Acropora species and the necessity to increase the taxonomic diversity of the collection. It also highlighted the need to increase geographic representation, even for the most well represented species. The inventory data will inform Taronga’s future research focus and sampling strategy to maximize genetic variation and biodiversity within the biobank and provide a test case for other practitioners implementing biobanking strategies for coral conservation around the world. Through co-investment and collaboration with research partners over the next decade, Taronga will prioritize and resource critical applied research and expand biobanking efforts to assist interventions for reef recovery and restoration.

Genetic Variation in Heat Tolerance of the Coral Platygyra Daedalea Indicates Potential for Adaptation to Ocean Warming - Holland Elder; Virginia M. Weis; Jose Montalvo-Proano; Veronique J. L. Mocellin; Andrew H. Baird; Eli Meyer; Line K. Bay (Frontiers in Marine Science, 2022)
Ocean warming represents the greatest threat to the persistence of reef ecosystems. Most coral populations are projected to experience temperatures above their current bleaching thresholds annually by 2050. Adaptation to higher temperatures is necessary if corals are to persist in a warming future. While many aspects of heat stress have been well studied, few data are available for predicting the capacity for adaptive cross-generational responses in corals. Consistent sets of heat tolerant genomic markers that reliably predict thermal tolerance have yet to be identified. To address this knowledge gap, we quantified the heritability and genetic variation associated with heat tolerance in Platygyra daedalea from the Great Barrier Reef. We tracked the survival of ten quantitative genetic crosses of larvae produced form six parental colonies in a heat tolerance selection experiment. We also identified allelic shifts in heat-selected (35°C) survivors compared with paired, non-selected controls (27°C). The narrow-sense heritability of survival under heat stress was 0.66 and a total of 1,069 single nucleotide polymorphisms (SNPs) were associated with different survival probabilities. While 148 SNPs were shared between several experimental crosses, no common SNPs were identified for all crosses, which suggests that specific combinations of many markers are responsible for heat tolerance. However, we found two regions that overlap with previously identified loci associated with heat tolerance in Persian Gulf populations of P. daedalea , which reinforces the importance of these markers for heat tolerance. These results illustrate the importance of high heritability and the complexity of the genomic architecture underpinning host heat tolerance. These findings suggest that this P. daedalea population has the genetic prerequisites for adaptation to increasing temperatures. This study also provides knowledge for the development of high throughput genomic tools which may screen for variation within and across populations to enhance adaptation through assisted gene flow and assisted migration.

Cryopreservation can assist gene flow on the Great Barrier Reef - Jonathan Daly; Rebecca J. Hobbs; Nikolas Zuchowicz; Justine K. O’Brien; Jessica Bouwmeester; Line Bay; Kate Quigley; Mary Hagedorn (Coral Reefs, 2022)
Maintaining genetic diversity and biodiversity is key to sustaining healthy ecosystems and their capacity for adaptation. Assisted Gene Flow (AGF) is a management approach to translocate adaptive genes among populations to restore faltering and at-risk habitats, especially on coral reefs. Cryopreserved sperm can facilitate AGF via selective breeding at a lower cost and with fewer risks than sourcing colonies from the wild or moving adult corals (translocation) . Here, we present a proof-of-concept study demonstrating that cryopreserved sperm from northern and central Great Barrier Reef (GBR) locations can be used to make intrapopulation and interpopulation crosses to underpin AGF. The results of this study support the importance of assessing the concentration of motile sperm in post-thaw samples, with a minimum of approximately 30,000 motile cryopreserved sperm per egg required to achieve fertilisation. Mean per cent motility values post-collection and without artificial activation (northern colonies 14 ± 3.2%; central colonies 19 ± 3.6%) were considerably lower than previous observations of sperm from Acropora tenuis on the Great Barrier Reef, and may represent a lag effect from recent ocean warming events at the level of coral populations. Coral reefs with relatively high species and genetic diversity and coral cover are good places to preserve biodiversity through cryopreservation. Such cryo-collections build a genetic resource to optimise strategies available to reef managers to support natural recovery rates and reef restoration and adaptation efforts.

Signatures of Adaptation and Acclimatization to Reef Flat and Slope Habitats in the Coral Pocillopora damicornis - Shelby R. Marhoefer; Kyall R. Zenger; Jan M. Strugnell; Murray Logan; Madeleine J. H. van Oppen; Carly D. Kenkel; Line K. Bay (Frontiers in Marine Science, 2021)
Strong population-by-habitat interactions across environmental gradients arise from genetic adaptation or acclimatization and represents phenotypic variation required for populations to respond to changing environmental conditions. As such, patterns of adaptation and acclimatization of reef-building corals are integral to predictions of the future of coral reefs under climate warming. The common brooding coral, Pocillopora damicornis , exhibits extensive differences in host genetic and microbial symbiont community composition between depth habitats at Heron Island in the southern Great Barrier Reef, Australia. An 18-month reciprocal field transplant experiment was undertaken to examine the environmental and genetic drivers behind variation in survival, weight gain, heat tolerance and algal symbiont community between the reef flat and slope habitats. We observed population-by-habitat interactions for in situ partial mortality and weight gain, where trait-related fitness of natives was greater than transplants in most cases, consistent with local adaptation. On average, flat colonies transplanted to the slope had a relatively low partial mortality but minimal weight gain, whereas slope colonies transplanted to the flat had relatively high partial mortality and average weight gain. Experimental heat tolerance was always higher in colonies sourced from the flat, but increased when slope colonies were transplanted to the flat, providing evidence of acclimatization in these colonies. The performance of certain slope to flat transplants may have been driven by each colony’s algal symbiont (Symbiodiniaceae) community, and flat variants were observed in a small number of slope colonies that either had a fixed flat composition before transplantation or shuffled after transplantation. Host genotypes of previously identified genetic outlier loci could not predict survival following transplantation, possibly because of low sample size and/or polygenic basis to the traits examined. Local environmental conditions and Symbiodiniaceae composition may provide insight into the adaptive potential to changing environmental conditions.

Variability in Fitness Trade-Offs Amongst Coral Juveniles With Mixed Genetic Backgrounds Held in the Wild - Kate M. Quigley; Magena Marzonie; Blake Ramsby; David Abrego; Grant Milton; Madeleine J. H. van Oppen; Line K. Bay (Frontiers in Marine Science, 2021)
Novel restoration methods are currently under consideration worldwide to help coral reefs recover or become more resilient to higher temperature stress. Critical field-based information concerning the paradigm of “local is best” is lacking for many methods; information which is essential to determine the risk and feasibility associated with restoration. One method involves breeding corals from different reef regions with expected variation in heat tolerance and moving those offspring to new locations to enhance offspring survival; thereby augmenting local stock to enhance survival for anticipated warming. In this study, surviving colonies from the 2016 to 2017 mass bleaching events on the Great Barrier Reef (GBR) were reproductively crossed and they included colonies sourced from northern (three) and central (two) reefs. The gravid colonies of Acropora tenuis were collected across 6° of latitude, and they were spawned to produce a total of 17 purebred and hybrid crosses. Juvenile corals (3,748 individual colonies settled on 1,474 terracotta tiles) were deployed to Davies reef in the central GBR after 4 months of aquarium rearing. Survival, growth, and coral colour (as a proxy for bleaching) were assessed after 0, 91, and 217 days of field deployment. Overall, a high percentage of juveniles (17% ± 2.5 SE) survived relative to expected survival at the final census. Survival was significantly higher for central purebred crosses, hybrid crosses had intermediate survival while northern purebreds had the lowest survival. Colour and growth rates (0.001−0.006 mm 2 day –1 ) were not significantly different amongst central, northern, or hybrid crosses but were of a reverse pattern compared to survival. On average, northern purebred crosses grew the fastest, followed by hybrid crosses, and then central purebred crosses. Modelled growth trajectories suggest that northern purebreds would take 8 years to grow to reproductive size, hybrids would take nine, and central purebreds would require 12. All deployed juvenile corals paled over time in the field although the colour of A. tenuis juveniles did not differ significantly amongst central, northern, or hybrid crosses. Growth and survival trade-off analysis showed that although most crosses did not outperform the native central juveniles, two of the eight hybrid crosses (SBxLS, DRxCU) demonstrated faster time to reproductive age and increased survival. Overall, reduced time to reach reproductive size and minimal trade-offs in at least two of the eight hybrids suggest that these crosses may accelerate and supplement recovery through natural re-seeding of genes sourced from northern reefs.

Global gene expression patterns in Porites white patch syndrome: Disentangling symbiont loss from the thermal stress response in reef‐building coral - Carly D. Kenkel; Veronique J. L. Mocellin; Line K. Bay (Molecular Ecology, 2020)
The mechanisms resulting in the breakdown of the coral symbiosis once the process of bleaching has been initiated remain unclear. Distinguishing the process of symbiont loss from the thermal stress response may shed light on the cellular and molecular pathways involved in each process. This study examined physiological changes and global gene expression patterns associated with white patch syndrome (WPS) in Porites lobata , which manifests in localized bleaching independent of thermal stress. In addition, a meta‐analysis of global gene expression studies in other corals and anemones was used to contrast differential regulation as a result of disease and thermal stress from patterns correlated with symbiotic state. Symbiont density, chlorophyll a content, holobiont productivity, instant calcification rate, and total host protein content were uniformly reduced in WPS relative to healthy tissue. While expression patterns associated with WPS were secondary to fixed effects of source colony, specific functional enrichments combined with a lack of immune regulation suggest that the viral infection putatively giving rise to this condition affects symbiont rather than host cells. Expression in response to WPS also clustered independently of patterns in white syndrome impacted A. hyacinthus , further supporting a distinct aetiology of this syndrome. Expression patterns in WPS‐affected tissues were significantly correlated with prior studies that examined short‐term thermal stress responses independent of symbiotic state, suggesting that the majority of expression changes reflect a nonspecific stress response. Across studies, the magnitude and direction of expression change among particular functional enrichments suggests unique responses to stressor duration and highlights distinct responses to bleaching in an anemone model.

Genome‐wide SNP analysis reveals an increase in adaptive genetic variation through selective breeding of coral - Kate M. Quigley; Line K. Bay; Madeleine J. H. van Oppen (Molecular Ecology, 2020)
Marine heat waves are increasing in magnitude, duration, and frequency as a result of climate change and are the principal global driver of mortality in reef‐building corals. Resilience‐based genetic management may increase coral heat tolerance, but it is unclear how temperature responses are regulated at the genome level and thus how corals may adapt to warming naturally or through selective breeding. Here we combine phenotypic, pedigree, and genomic marker data from colonies sourced from a warm reef on the Great Barrier Reef reproductively crossed with conspecific colonies from a cooler reef to produce combinations of warm purebreds and warm‐cool hybrid larvae and juveniles. Interpopulation breeding created significantly greater genetic diversity across the coral genome compared to breeding between populations and maintained diversity in key regions associated with heat tolerance and fitness. High‐density genome‐wide scans of single nucleotide polymorphisms (SNPs) identified alleles significantly associated with larval families reared at 27.5°C (87–2,224 loci), including loci putatively associated with proteins involved in responses to heat stress (cell membrane formation, metabolism, and immune responses). Underlying genetics of these families explained 43% of PCoA multilocus variation in survival, growth, and bleaching responses at 27.5°C and 31°C at the juvenile stage. Genetic marker contribution to total variation in fitness traits (narrow‐sense heritability) was high for survival but not for growth and bleaching in juveniles, with heritability of these traits being higher at 31°C relative to 27.5°C. While based on only a limited number of crosses, the mechanistic understanding presented here demonstrates that allele frequencies are affected by one generation of selective breeding, key information for the assessments of genetic intervention feasibility and modelling of reef futures.

Symbiont community diversity is more variable in corals that respond poorly to stress - Lauren I. Howe‐Kerr; Benedicte Bachelot; Rachel M. Wright; Carly D. Kenkel; Line K. Bay; Adrienne M. S. Correa (Global Change Biology, 2020)
Coral reefs are declining globally as climate change and local water quality press environmental conditions beyond the physiological tolerances of holobionts—the collective of the host and its microbial symbionts. To assess the relationship between symbiont composition and holobiont stress tolerance, community diversity metrics were quantified for dinoflagellate endosymbionts (Family: Symbiodiniaceae) from eight Acropora millepora genets that thrived under or responded poorly to various stressors. These eight selected genets represent the upper and lower tails of the response distribution of 40 coral genets that were exposed to four stress treatments (and control conditions) in a 10‐day experiment. Specifically, four ‘best performer’ coral genets were analyzed at the end of the experiment because they survived high temperature, high p CO 2 , bacterial exposure, or combined stressors, whereas four ‘worst performer’ genets were characterized because they experienced substantial mortality under these stressors. At the end of the experiment, seven of eight coral genets mainly hosted Cladocopium symbionts, whereas the eighth genet was dominated by both Cladocopium and Durusdinium symbionts. Symbiodiniaceae alpha and beta diversity were higher in worst performing genets than in best performing genets. Symbiont communities in worst performers also differed more after stress exposure relative to their controls (based on normalized proportional differences in beta diversity), than did best performers. A generalized joint attribute model estimated the influence of host genet and treatment on Symbiodiniaceae community composition and identified strong associations among particular symbionts and host genet performance, as well as weaker associations with treatment. Although dominant symbiont physiology and function contribute to host performance, these findings emphasize the importance of symbiont community diversity and stochasticity as components of host performance. Our findings also suggest that symbiont community diversity metrics may function as indicators of resilience and have potential applications in diverse disciplines from climate change adaptation to agriculture and medicine.

Positive genetic associations among fitness traits support evolvability of a reef‐building coral under multiple stressors - Rachel M. Wright; Hanaka Mera; Carly D. Kenkel; Maria Nayfa; Line K. Bay; Mikhail V. Matz (Global Change Biology, 2019)
Climate change threatens organisms in a variety of interactive ways that requires simultaneous adaptation of multiple traits. Predicting evolutionary responses requires an understanding of the potential for interactions among stressors and the genetic variance and covariance among fitness‐related traits that may reinforce or constrain an adaptive response. Here we investigate the capacity of Acropora millepora , a reef‐building coral, to adapt to multiple environmental stressors: rising sea surface temperature, ocean acidification, and increased prevalence of infectious diseases. We measured growth rates (weight gain), coral color (a proxy for Symbiodiniaceae density), and survival, in addition to nine physiological indicators of coral and algal health in 40 coral genets exposed to each of these three stressors singly and combined. Individual stressors resulted in predicted responses (e.g., corals developed lesions after bacterial challenge and bleached under thermal stress). However, corals did not suffer substantially more when all three stressors were combined. Nor were trade‐offs observed between tolerances to different stressors; instead, individuals performing well under one stressor also tended to perform well under every other stressor. An analysis of genetic correlations between traits revealed positive covariances, suggesting that selection to multiple stressors will reinforce rather than constrain the simultaneous evolution of traits related to holobiont health (e.g., weight gain and algal density). These findings support the potential for rapid coral adaptation under climate change and emphasize the importance of accounting for corals’ adaptive capacity when predicting the future of coral reefs.

Temporal and spatial variation in fatty acid composition in Acropora tenuis corals along water quality gradients on the Great Barrier Reef, Australia - Melissa M. Rocker; David S. Francis; Katharina E. Fabricius; Bette L. Willis; Line K. Bay (Coral Reefs, 2019)

Contrasting effects of Symbiodinium identity on coral host transcriptional profiles across latitudes - Sarah J. Barfield; Galina V. Aglyamova; Line K. Bay; Mikhail V. Matz (Molecular Ecology, 2018)
Reef‐building corals can increase their resistance to heat‐induced bleaching through adaptation and acclimatization and/or by associating with a more thermo‐tolerant strain of algal symbiont ( Symbiodinium sp.). Here, we show that these two adaptive pathways interact. We collected Acropora millepora corals from two contrasting thermal environments on the Great Barrier Reef: cooler, mid‐latitude Orpheus Island, where all corals hosted a heat‐sensitive clade C Symbiodinium , and warmer, low‐latitude Wilkie Island, where corals hosted either a clade C or a more thermo‐tolerant clade D. Corals were kept in a benign common garden to reveal differences in baseline gene expression, reflecting prior adaptation/long‐term acclimatization. Model‐based analysis identified gene expression differences between Wilkie and Orpheus corals that were negatively correlated with previously described transcriptome‐wide signatures of heat stress, signifying generally elevated thermotolerance of Wilkie corals. Yet, model‐free analyses of gene expression revealed that Wilkie corals hosting clade C were distinct from Wilkie corals hosting clade D, whereas Orpheus corals were more variable. Wilkie corals hosting clade C symbionts exhibited unique functional signatures, including downregulation of histone proteins and ion channels and upregulation of chaperones and RNA processing genes, putatively representing constitutive “frontloading” of stress response genes. Furthermore, clade C Symbiodinium exhibited constitutive expression differences between Wilkie and Orpheus, indicative of contrasting life history strategies. Our results demonstrate that hosting alternative Symbiodinium types is associated with different pathways of local adaptation for the coral host. These interactions could play a significant role in setting the direction of genetic adaptation to global warming in the two symbiotic partners.

Adaptation to reef habitats through selection on the coral animal and its associated microbiome - Madeleine J. H. van Oppen; Pim Bongaerts; Pedro Frade; Lesa M. Peplow; Sarah E. Boyd; Hieu T. Nim; Line K. Bay (Molecular Ecology, 2018)
Spatially adjacent habitats on coral reefs can represent highly distinct environments, often harbouring different coral communities. Yet, certain coral species thrive across divergent environments. It is unknown whether the forces of selection are sufficiently strong to overcome the counteracting effects of the typically high gene flow over short distances, and for local adaptation to occur. We screened the coral genome (using restriction site‐associated sequencing) and characterized both the dinoflagellate photosymbiont‐ and tissue‐associated prokaryote microbiomes (using metabarcoding) of a reef flat and slope population of the reef‐building coral, Pocillopora damicornis , at two locations on Heron Island in the southern Great Barrier Reef. Reef flat and slope populations were separated by

Functional genomic analysis of corals from natural CO 2 ‐seeps reveals core molecular responses involved in acclimatization to ocean acidification - Carly D. Kenkel; Aurelie Moya; Julia Strahl; Craig Humphrey; Line K. Bay (Global Change Biology, 2018)
Little is known about the potential for acclimatization or adaptation of corals to ocean acidification and even less about the molecular mechanisms underpinning these processes. Here, we examine global gene expression patterns in corals and their intracellular algal symbionts from two replicate population pairs in Papua New Guinea that have undergone long‐term acclimatization to natural variation in pCO 2 . In the coral host, only 61 genes were differentially expressed in response to pCO 2 environment, but the pattern of change was highly consistent between replicate populations, likely reflecting the core expression homeostasis response to ocean acidification. Functional annotations highlight lipid metabolism and a change in the stress response capacity of corals as key parts of this process. Specifically, constitutive downregulation of molecular chaperones was observed, which may impact response to combined climate change‐related stressors. Elevated CO 2 has been hypothesized to benefit photosynthetic organisms but expression changes of in hospite Symbiodinium in response to acidification were greater and less consistent among reef populations. This population‐specific response suggests hosts may need to adapt not only to an acidified environment, but also to changes in their Symbiodinium populations that may not be consistent among environments, adding another challenging dimension to the physiological process of coping with climate change.

Temperature and Water Quality-Related Patterns in Sediment-Associated Symbiodinium Communities Impact Symbiont Uptake and Fitness of Juveniles in the Genus Acropora - Kate M. Quigley; Line K. Bay; Bette L. Willis (Frontiers in Marine Science, 2017)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Does genetic distance between parental species influence outcomes of hybridization among coral reef butterflyfishes? - Stefano R. Montanari; Jean‐Paul A. Hobbs; Morgan S. Pratchett; Line K. Bay; Lynne Van Herwerden (Molecular Ecology, 2014)
Christmas Island is located at the overlap of the Indian and Pacific Ocean marine provinces and is a hot spot for marine hybridization. Here, we evaluate the ecological framework and genetic consequences of hybridization between butterflyfishes Chaetodon guttatissimus and Chaetodon punctatofasciatus . Further, we compare our current findings to those from a previous study of hybridization between Chaetodon trifasciatus and Chaetodon lunulatus . For both species groups, habitat and dietary overlap between parental species facilitate frequent heterospecific encounters. Low abundance of potential mates promotes heterospecific pair formation and the breakdown of assortative mating. Despite similarities in ecological frameworks, the population genetic signatures of hybridization differ between the species groups. Mitochondrial and nuclear data from C. guttatissimus × C. punctatofasciatus (1% divergence at cyt b ) show bidirectional maternal contributions and relatively high levels of introgression, both inside and outside the Christmas Island hybrid zone. In contrast, C. trifasciatus × C. lunulatus (5% cyt b divergence) exhibit unidirectional mitochondrial inheritance and almost no introgression. Back‐crossing of hybrid C. guttatissimus × C. punctatofasciatus and parental genotypes may eventually confound species‐specific signals within the hybrid zone. In contrast, hybrids of C. trifasciatus and C. lunulatus may coexist with and remain genetically distinct from the parents. Our results, and comparisons with hybridization studies in other reef fish families, indicate that genetic distance between hybridizing species may be a factor influencing outcomes of hybridization in reef fish, which is consistent with predictions from terrestrially derived hybridization theory.

Isolation and characterization of twenty microsatellite markers for the study of hybridization in butterflyfish of the genus Chaetodon - Stefano R. Montanari; Michael G. Gardner; Jean-Paul A. Hobbs; Morgan S. Pratchett; Line K. Bay; Lynne van Herwerden (Conservation Genetics Resources, 2013)

Spatial and temporal genetic structure of S ymbiodinium populations within a common reef‐building coral on the G reat B arrier R eef - Emily J. Howells; Bette L. Willis; Line K. Bay; Madeleine J. H. van Oppen (Molecular Ecology, 2013)
The dinoflagellate photosymbiont Symbiodinium plays a fundamental role in defining the physiological tolerances of coral holobionts, but little is known about the dynamics of these endosymbiotic populations on coral reefs. Sparse data indicate that Symbiodinium populations show limited spatial connectivity; however, no studies have investigated temporal dynamics for in hospite Symbiodinium populations following significant mortality and recruitment events in coral populations. We investigated the combined influences of spatial isolation and disturbance on the population dynamics of the generalist Symbiodinium type C2 ( ITS 1 rDNA ) hosted by the scleractinian coral Acropora millepora in the central Great Barrier Reef. Using eight microsatellite markers, we genotyped Symbiodinium in a total of 401 coral colonies, which were sampled from seven sites across a 12‐year period including during flood plume–induced coral bleaching. Genetic differentiation of Symbiodinium was greatest within sites, explaining 70–86% of the total genetic variation. An additional 9–27% of variation was explained by significant differentiation of populations among sites separated by 0.4–13 km, which is consistent with low levels of dispersal via water movement and historical disturbance regimes. Sampling year accounted for 6–7% of total genetic variation and was related to significant coral mortality following severe bleaching in 1998 and a cyclone in 2006. Only 3% of the total genetic variation was related to coral bleaching status, reflecting generally small (8%) reductions in allelic diversity within bleached corals. This reduction probably reflected a loss of genotypes in hospite during bleaching, although no site‐wide changes in genetic diversity were observed. Combined, our results indicate the importance of disturbance regimes acting together with limited oceanographic transport to determine the genetic composition of Symbiodinium types within reefs.

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Isolation and characterization of 29 microsatellite loci for studies of population connectivity in the butterflyfishes Chaetodon trifascialis and Chaetodon lunulatus - Rebecca J. Lawton; Morgan S. Pratchett; Line K. Bay (Conservation Genetics Resources, 2010)

Isolation, characterisation and cross amplification of thirteen microsatellite loci for coral endo-symbiotic dinoflagellates (Symbiodinium clade C) - Line Kolind Bay; Emily J. Howells; Madeleine J. H. van Oppen (Conservation Genetics Resources, 2009)

Microarray analysis reveals transcriptional plasticity in the reef building coral Acropora millepora - LINE K. BAY; KARIN E. ULSTRUP; H. BJØRN NIELSEN; HANNE JARMER; NICOLAS GOFFARD; BETTE L. WILLIS; DAVID J. MILLER; MADELEINE J. H. VAN OPPEN (Molecular Ecology, 2009)
We investigated variation in transcript abundance in the scleractinian coral, Acropora millepora, within and between populations characteristically exposed to different turbidity regimes and hence different levels of light and suspended particulate matter. We examined phenotypic plasticity by comparing levels of gene expression between source populations and following 10 days of acclimatization to a laboratory environment. Analyses of variance revealed that 0.05% of genes were differentially expressed between source populations, 1.32% following translocation into a common laboratory and 0.07% in the interaction (source population‐dependent responses to translocation). Functional analyses identified an over‐representation of differentially expressed genes associated with metabolism and fluorescence categories (primarily downregulated), and environmental information processing (primarily upregulated) following translocation to a lower light and turbidity environment. Such metabolic downregulation may indicate nonoxidative stress, hibernation or caloric restriction associated with the changed environmental conditions. Green fluorescent protein‐related genes were the most differentially expressed and were exclusively downregulated; however, green fluorescent protein levels remained unchanged following translocation. Photophysiological responses of corals from both locations were characterized by a decline when introduced to the common laboratory environment but remained healthy ( F v / F m > 0.6). Declines in total lipid content following translocation were the greatest for inshore corals, suggesting that turbid water corals have a strong reliance on heterotrophic feeding.

Development and characterization of microsatellite markers for parentage analyses of the coral reef damselfish (Pomacentrus amboinensis: Pomacentridae) - Katherine P. Munkres; Line K. Bay; Dean R. Jerry; Mark I. McCormick; Lynne Van Herwerden (Conservation Genetics, 2007)